The Influence of Social Media on Student Learning Opportunities and Challenges in the Digital Age - dewa, sufa; Seto, Haryo (English Education Department, 2025)
This study examined how students' perceptions, experiences, and recommendations illuminate the impact of social media on students' learning. Qualitative research design was used and data was collected using open-ended questionnaires with 11 students at Universitas Tidar. Thematic analyses were used to ascertain that social media sites, such as YouTube, Instagram, TikTok, and Reddit, were an important part of their learning practices and processes, and that the social media sites were important for student access to learning materials, online conversation, and collaboration with peers. However, students were also aware of the difficulties with social media, namely digital distraction and peer pressure for social validation. Overall, students thought social media was a positive additive to their education, despite the challenges of social media. Overall, our findings suggest that educational social media utilization needs to be intentional and deliberate and we encourage educators to use social media for content creation that students engage with, and that matches their own preferences for digital engagement and learning.